The Influence Of Capital, Information Technology, and Work Experience On The Income Of Perak Smes, Celuk Village, Sukawati District - I Gede Wahyu Indrayana; Ida Bagus Purbadharmaja (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The Gianyar Regency area, especially the Sukawati sub-district, is considered to have become the center of silver crafts in the Bali region, which is found precisely in Celuk Village as a silver craft producing area that has existed since 1976, but in the current conditions Celuk Village is experiencing a decline in the number of established businesses. , the amount of production, and also the workforce, this condition seems to occur from year to year, thus triggering a decrease in the amount of income of business actors. The purpose of this research is to analyze the influence of capital, information technology and work experience on the income of silver SMEs in Celuk Village, Sukawati District. This research is included in the quantitative research category. The total population and sample data that supports this research is 150 respondents. The research results show that capital, information technology and work experience have a significant positive effect on the income of Perak SMEs in Celuk Village, Sukawati District. The implication obtained from this series of activities is that capital, information technology, and work experience have successfully contributed to the income of Perak SMEs. The results of this activity can be used as a guide or reference for other SMEs in supporting increased income by paying more attention to capital, information technology and work experience, because the greater the amount of income earned, the greater the ability of a business to function automatically. finance all business expenses.